Trends and patterns in vaccination objection, Australia, 2002–2013. Issue 7 (18th April 2016) - Beard, Frank H; Hull, Brynley P; Leask, Julie; Dey, Aditi; McIntyre, Peter B
Abstract: Objectives: To examine geographic and demographic trends in objection to vaccination in Australia. Design: Cross‐sectional analysis of Australian Childhood Immunisation Register (ACIR) data (2002–2013) for children aged 1–6 years. Main outcome measures: Immunisation status according to whether an objection had been registered, and remoteness and socio‐economic status of area of residence. Registration of children with Medicare after 12 months of age was used as a proxy indicator of being overseas‐born. Results: The proportion of children affected by a registered vaccination objection increased from 1.1% in 2002 to 2.0% in 2013. Children with a registered objection were clustered in regional areas. The proportion was lower among children living in areas in the lowest decile of socio‐economic status (1.1%) than in areas in the highest socio‐economic decile (1.9%). The proportion not affected by a recorded objection but who were only partly vaccinated for vaccines due at 2, 4 and 6 months of age was higher among those in the lowest decile (5.0% v 3.4%), suggesting problems of access to health services, missed opportunities, and logistic difficulties. The proportion of proxy overseas‐born for whom neither vaccinations nor an objection were recorded was 14 times higher than for other children (17.1% v 1.2%). These children, who are likely to be vaccinated although this is not recorded on the ACIR, resided predominantly in major cities. Conclusions: There was a small increase in registered objection rates since 2002. We estimate that 3.3% of children are affected by registered or presumptive (unregistered) vaccination objection, which suggests that the overall impact of vaccination objection on vaccination rates has remained largely unchanged since 2001. Incomplete records, barriers to access, and missed opportunities are likely to be responsible for most other deficiencies in vaccination coverage.